Oral Health Literacy and Oral Health Behavior of Senior Medical and Pharmacy Students - Reza Yazdani; SiminZahra Mohebbi; Soheil Chehree (Islamic Dental Association of Iran, 2017)
Background and Aim: Oral health literacy plays an important role in oral health promotion. This study aimed to assess the level of oral health literacy of senior medical and pharmacy students. Materials and Methods: This cross-sectional study was conducted on senior medical and pharmacy students (n=300) of Tehran University of Medical Sciences in 2015. The oral health literacy-adult questionnaire (OHL-AQ) was used for data collection. This questionnaire has 17 items in four sections. The first section relates to the assessment of the perception of oral health. The second section is for the assessment of the ability to calculate values related to antibiotic and mouthwash prescriptions. The third section assesses the efficacy of communication skills, and the fourth section is about decision-making with regard to oral health problems. Chi-square and linear regression were used for descriptive analyses. Results: The mean score of oral health literacy was 12.093.85 for medical students and 10.484.29 for pharmacy students. University degree of the father (P<0.001) and being a medical student (P=0.002) were significantly correlated with a higher level of oral health literacy. The comparison of the mean score of oral health literacy and its associa-tion with oral health behavior showed a significant correlation between a high level of oral health literacy and a higher frequency of tooth brushing, use of toothpaste, regular dental visits, and dental visits during the last 1-2 years (P=0.001). Conclusion: Considering the moderate level of oral health literacy of medical and pharmacy students, it is necessary to include oral health topics in the curricula of medi-cal and pharmacy schools.